Mefloquine targets the Plasmodium falciparum 80S ribosome to inhibit protein synthesis - Wong,W; Bai,XC; Sleebs,B; Triglia,T; Brown,A; Thompson,JK; Jackson,KE; Hanssen,E; Marapana,DS; Fernandez,I; Ralph,SA; Cowman,AF; et al. (Nature Microbiology, 2017)
Malaria control is heavily dependent on chemotherapeutic agents for disease prevention and drug treatment. Defining the mechanism of action for licensed drugs, for which no target is characterized, is critical to the development of their second-generation derivatives to improve drug potency towards inhibition of their molecular targets. Mefloquine is a widely used antimalarial without a known mode of action. Here, we demonstrate that mefloquine is a protein synthesis inhibitor. We solved a 3.2 Å electron cryo-microscopy structure of the Plasmodium falciparum 80S-ribosome with the (+)-mefloquine enantiomer bound to the ribosome GTPase-associated center. Mutagenesis of mefloquine-binding residues generates parasites with increased resistance, confirming the parasite-killing mechanism. Furthermore, structure-guided derivatives with an altered piperidine group, predicted to improve binding, show enhanced parasiticidal effect. These data reveal one possible mode of action for mefloquine and demonstrate the vast potential of cryo-EM to guide the development of mefloquine derivatives to inhibit parasite protein synthesis.